Implementasi Nilai-Nilai Kearifan Lokal Masyarakat Ngata Toro Dalam Membangun Literasi Ekologi Pada Siswa SMAN 5 SIGI - Zumrotin Nisa'; Rendra Zainal Maliki; Suwarni Suwarni; Safirah Nur Alya; Raehan Raehan (STKIP Singkawang, 2006)
This study aims to implement the values of local wisdom of the Ngata Toro community in developing ecological literacy among students at SMAN 5 Sigi. The study employed a quantitative approach using a quasi-experimental design, namely an untreated control group design with dependent pretest and posttest samples. The research population consisted of Class XI IPS 1 with 30 students as the experimental group and Class XI IPS 2 with 28 students as the control group. The research instrument was a multiple-choice test consisting of 20 items. The results of hypothesis testing (t-test) using IBM SPSS version 20 indicated that the mean posttest score of the experimental group was 79.17, while that of the control group was 60.18. The obtained Sig. (2-tailed) value was 0.001, which is lower than 0.05 (Sig. 0.001 < 0.05), indicating that H₀ was rejected and Hₐ was accepted. It can be concluded that the implementation of the local wisdom values of the Ngata Toro community has a significant effect on improving ecological literacy among students at SMAN 5 Sigi.